2012
DOI: 10.1089/aid.2011.0259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation, Treatment, and Outcomes Among 65 Patients with HIV-Associated Lymphoma Treated at the University of North Carolina, 2000–2010

Abstract: HIV increases risk of non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma (HL). The effect of HIV on presentation, treatment, and outcomes of NHL and HL in routine care in the combination antiretroviral therapy (cART) merits further characterization. We performed a retrospective analysis of HIV-infected patients with NHL and HL receiving care at the University of North Carolina at Chapel Hill from January 1, 2000 until December 31, 2010. Statistical analyses were conducted using SAS, version 9.2 (SAS Institute Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This finding is consistent with other smaller studies that have found similarly high rates of stage III/IV disease: 88% of 26 NHL cases [14], 74% of 34 DLBCL cases [15] and 71% of 97 DLBCL cases [16]. It is unclear why HIV-infected patients tend to have more advanced disease at presentation, but biologic (immunosuppression allowing unchecked tumor growth or more aggressive tumor biology) and sociologic (delayed presentation to care) mechanisms are both possible, whether HIV-associated lymphomas 5…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with other smaller studies that have found similarly high rates of stage III/IV disease: 88% of 26 NHL cases [14], 74% of 34 DLBCL cases [15] and 71% of 97 DLBCL cases [16]. It is unclear why HIV-infected patients tend to have more advanced disease at presentation, but biologic (immunosuppression allowing unchecked tumor growth or more aggressive tumor biology) and sociologic (delayed presentation to care) mechanisms are both possible, whether HIV-associated lymphomas 5…”
Section: Discussionsupporting
confidence: 93%
“…Although access to death certificates or Maryland state data was not possible in this study, prior studies [14,22,27] have all found the vast majority of deaths in patients dually diagnosed with HIV and cancer are from progression of underlying cancer rather than infections or treatment-related complications and toxicities.…”
mentioning
confidence: 97%
“…Discordant findings may partially reflect differences in the HIV-infected populations and health-care systems in the United States and Europe, respectively. Other reasons for a lack of survival improvement may include continued presentation with advanced stage and poor performance status (25,27,33), difficulty achieving stage-appropriate chemotherapy cumulative dose and dose intensity (25,33), reduced effectiveness or greater toxicity of chemotherapy due to ART interactions (34), discontinuity or suboptimal concentrations of ART due to chemotherapy interactions (33,34), diminished immunologic response against malignant lymphocytes, intrinsically aggressive tumor biology, and mortality from lymphoma-unrelated causes. Treatment incorporating more intensive first-line and salvage chemotherapy, immunotherapy, radiotherapy, and high-dose therapy with autologous stem cell rescue may also be less frequently used in HIV-infected patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…PCNSL usually occurs in patients with advanced immunosuppressed status and low CD4+ lymphocyte counts (<50 cells/µL), and frequently with an AIDS-defining illness before lymphoma diagnosis [ 31 , 45 , 64 , 65 , 66 ]. In this regard, low CD4+ lymphocyte counts and high HIV load are associated with a worse outcome in patients with PCNSL [ 31 , 42 ].…”
Section: Implications Of Epstein–barr Virus In the Different Hiv-related Lymphoma Typesmentioning
confidence: 99%